Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan dan Loyalitas Pengguna Kawasan Industri - Lesmana, Hendra; Hadiwidjojo, Djumilah (Jurnal Aplikasi Manajemen, 2014)
The objective of this research to measure empirically the effect of service quality which consists of seven dimensions including physical evidence, responsiveness, reliability, competence, confidence, recovery of complaints and external empathy to the satisfaction and loyalty of user of industrial area. The results of this research are expected to contribute in enriching the repertoire of knowledge in the field of marketing, especially the theory of marketing services business, especially in the industrial area, which is expected to provide benefits to academics and practitioners.This research using industrial area throughout the region that extends around the right side of the road toll Jakarta-Cikampek, as the object of researchis the company's industrial estate users. The selection was randomly sampled using a systematic sampling technique. Collecting data using a questionnaire filled out by the company's leaders industrial users, which is related to the level of director or manager. Data analysis using Structural Equation Modelling techniques. The results of this study found that: The quality of service on the company's industrial estate consisting of seven dimensions: physical evidence, responsiveness, reliability, competence, confidence and attention out to the strengthening of user satisfaction and loyalty of the industrial estate. Means the quality of service which consists of seven dimensions: physical evidence, responsiveness, reliability, competence, confidence, recovery of complaints, and external empathy can be carried out well and can improve user satisfaction and loyalty in the industrial estate. Quality of service on the company improve the industrial estate of satisfaction, but not to the industrial estate user loyalty. Conclusions are contained mean that although the quality of service is done well and able to improve satisfaction but not necessarily be able to increase loyalty of user of industrial estate.